Analysis of complete genomic sequences of isolates of the sweet potato feathery mottle virus strains C and EA: molecular evidence for two distinct potyvirus species and two P1 protein domains - Untiveros, M.; Quispe, D.; Kreuze, Jan F. (Springer, 2010)
The complete nucleotide sequence of the isolate C1 of Sweet potato feathery mottle virus (SPFMV) strain C and the 5' region of several other strains were determined and analyzed together with the sequences of isolates representing the EA, RC and O strains. This provided molecular evidence for the reclassification of SPFMV strains into two species and the occurrence of a complex recombinant isolate. Analysis also revealed a hypervariable domain in the P1 protein, which separates an N-terminal region unique to SPFMV and members of the ipomovirus species Sweet potato mild mottle virus from the C-terminal protease domain, which is conserved among all potyviruses.